Ambient black carbon particles reach the fetal side of human placenta - Bové, Hannelore; Bongaerts, Eva; Slenders, Eli; Bijnens, Esmée M.; Saenen, Nelly D.; Gyselaers, Wilfried; Van Eyken, Peter; Plusquin, Michelle; Roeffaers, Maarten B. J.; Ameloot, Marcel; Nawrot, Tim S. (Nature communications, 2019)
Particle transfer across the placenta has been suggested but to date, no direct evidence in real-life, human context exists. Here we report the presence of black carbon (BC) particles as part of combustion-derived particulate matter in human placentae using white-light generation under femtosecond pulsed illumination. BC is identified in all screened placentae, with an average (SD) particle count of 0.95 × 10 4 (0.66 × 10 4 ) and 2.09 × 10 4 (0.9 × 10 4 ) particles per mm 3 for low and high exposed mothers, respectively. Furthermore, the placental BC load is positively associated with mothers’ residential BC exposure during pregnancy (0.63–2.42 µg per m 3 ). Our finding that BC particles accumulate on the fetal side of the placenta suggests that ambient particulates could be transported towards the fetus and represents a potential mechanism explaining the detrimental health effects of pollution from early life onwards. Exposure to air pollution during pregnancy has been associated with impaired birth outcomes. Here, Bové et al. report evidence of black carbon particle deposition on the fetal side of human placentae, including at early stages of pregnancy, suggesting air pollution could affect birth outcome through direct effects on the fetus.